Assessment of knowledge, practices, and attitude of hand-hygiene among university nursing and optometry undergraduate students in their final year of training - Ayyappan, Janitha Plackal; Varghese, Virgina; Ismail, Galal Mohammed (International Journal of Research in Counseling and Education, 2021)
Safe Hand hygiene practice is considered an essential component of patient safety. However, especially when it comes to health professionals, students are exposed to their clinical practice in the first few years. This condition accelerates the chances of getting infection via cross-transmission of hands through the healthcare worker to the patient is most common. Therefore, a quantitative cross-sectional questionnaire-based survey was carried out to investigate the level of knowledge, practices, and attitude of Hand hygiene among university nursing and optometry undergraduate students in their final year of training. A total of one hundred and forty-three subjects took part in the survey of 73 nursing students and 70 optometry students. Fisher’s exact test was applied to test the level of knowledge on practice and attitude.Furthermore, the correlation coefficient r=-1 to +1 with P>0.05 was obtained. To add, using an observational checklist will be the ideal way to assess the hand hygiene practice in the clinical area. Moreover, add a mandatory component as patient safety to the curricula of the undergraduate students of allied health will enhance patient safety more effectively.